Coupling of heterogeneous advanced oxidation processes and photocatalysis in efficient degradation of tetracycline hydrochloride by Fe-based MOFs: Synergistic effect and degradation pathway - Zhang, Ying; Zhou, Jiabin; Chen, Xin; Wang, Luo; Cai, Weiquan (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
•Heterogeneous AOP and photocatalysis were coupled for efficient degradation of TC.•The introduction of PS effectively suppressed the recombination of charge carries.•Photogenerated electron can activate PS to generate SO4−• radicals.•The degradation pathways for TC are investigated through LC-MS technique. In this work, a Fe-based metal organic frameworks (MIL-88A) has been synthesized through a hydrothermal method and adopted as a high-efficiency catalyst for photocatalysis (PC) coupled with sulfate radical-based advanced oxidation processes (SR-AOPs) to degrade tetracycline hydrochloride (TC-HCl) under visible light irradiation. The effects of MIL-88A/persulfate (PS) molar ratio, initial solution pH and catalyst dosage were studied. The results indicated that the combining of the photocatalysis and SR-AOPs could remarkably enhance TC degradation and 200 mg/L 100 mL TC could be degraded completely at 0.25 g/L MIL-88A, unadjusted pH value and 4 mM PS in 80 mins. The results of scavenging experiments and ESR analysis demonstrated that SO4−• and •O2– radicals were the predominant radicals for the TC degradation. The significant improvement of degradation rate in MIL-88A/PS/Vis process is attributed to the following two factors: (1) as a photocatalyst, MIL-88A could be excited by visible light, therefore photogenerated electrons (e−) on the conduction band (CB) of MIL-88A could be trapped by PS to generate SO4−• radicals. In this process, PS acted as an electron acceptor and the electron/hole recombination was suppressed leading to the enhanced photocatalyst efficiency; (2) The PS can be activated not only by photoelectrons but also Fe (III) in MIL-88A leads to the generation of SO4−• radicals more rapidly and easily. A possible mechanism and degradation pathway for TC was proposed based on the trapping/ESR experiments and liquid chromatography-mass spectrometry (LC-MS) analysis. This work proposed a new idea and method in combining two oxidation processes in degradation of organic pollutants thus could be potentially used in environmental purification.